TALENT MANAGEMENT AS CORRELATE OF EMPLOYEEPLACEMENT AND RETENTION IN PUBLIC UNIVERSITIES INSOUTHEAST NIGERIA (NAU Journal of Technology and Vocational Education, 2024)
This study talent as correlate of employee placement and retention in universities in South EastNigeria. Two research questions guided the study and two hypotheses were tested at 0.05 level ofsignificance. Correlational research design was employed for the study. The population consistedof819 senior university non-teaching staff. A sample of 249 senior non-teaching staff of publicuniversities in South-east Nigeria was used for the study. The 249 staff were sampled usingproportionate stratified sampling technique. The instrument for data collection was a structuredquestionnaire divided into Sections ‘A’ and ‘B’. Section ‘A’ contains demographic informationofrespondents while Section ‘B’ was categorized into nine clusters to cover the seven components oftalent management, Employee placement and Employee Retention. The instruments were validatedusing the opinions of experts and their reliability coefficients were .88 and .93, these were realizedusing Cronbach alpha. Data collected were analyzed using Pearson Product Moment CorrelationCoefficient (PPMC) to answer the research questions and Multivariate Simple Linear Regression(MSLR) with Fisher-Z test to test the hypotheses. Data analysis revealed that talent management;compensation planning and career development correlate employee placement and retention. Theresult also revealed that the ownership of the universities (Federal or State) determined staff responsesbased on the two components discussed in this study. Based on the findings, the study recommendedthat the universities managements should provide adequate and appropriate compensation plans bothin cash, materials and conducive atmosphere for staff; in service trainings to develop and channel thetalents of staff towards the attainment of institutions’’ goals.
Keywords: Talent management; employee placement and employee retention